2018
DOI: 10.1097/md.0000000000010055
|View full text |Cite
|
Sign up to set email alerts
|

MRI and CT contrast media extravasation

Abstract: Background:This systematic review combines data from multiple papers on contrast media extravasation to identify factors contributing to increased extravasation risk.Methods:Data were extracted from 17 papers reporting 2191 extravasations in 1,104,872 patients (0.2%) undergoing computed tomography (CT) or magnetic resonance imaging (MRI).Results:Extravasation rates were 0.045% for gadolinium-based contrast agents (GBCA) and nearly 6-fold higher, 0.26% for iodinated contrast agents. Factors associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Extravasation rates are 0.045% for gadolinium-based contrast agents and nearly six-fold higher, at 0.26%, for iodinated contrast agents. 17 Extravasation is considered to be caused by disruption of the blood–brain barrier or blood–CSF barrier. 18 , 19 Most extravasations are well-tolerated and resolve without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extravasation rates are 0.045% for gadolinium-based contrast agents and nearly six-fold higher, at 0.26%, for iodinated contrast agents. 17 Extravasation is considered to be caused by disruption of the blood–brain barrier or blood–CSF barrier. 18 , 19 Most extravasations are well-tolerated and resolve without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 Most extravasations are well-tolerated and resolve without surgical intervention. 17 In the present case, a differential diagnosis of hemorrhage was able to be eliminated with the following five points: (1) the high-density shadow on CT scans had rapid dissolution; (2) there was drainage of clear fluid; (3) the structure of the left basal ganglia remained intact after the high-density shadow disappeared; (4) a scant amount of red blood cells were found in the routine CSF examination; and (5) the HU of the high-density shadow on CT was markedly higher than that of a hematoma (approximately 90 HU, on average). The contrast agent that was used in our patient was composed of iodixanol (Visipaque), which is relatively viscous.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging is one of the most powerful diagnostic tools available in clinical use [ 1 , 2 , 3 , 4 ]. Almost a third of all MR scans are performed using an MR contrast agent, which can be administered orally, intravenously, or through inhalation in order to enhance resulting diagnostic images [ 2 , 5 , 6 , 7 ]. These agents can alter the magnetic moment of 1 H in a local tissue microenvironment to either increase or decrease the MR signal on images, depending on the contrast agent used and the imaging parameters [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although gadolinium extravasation in MRI is less commonly reported, a recent systemic review reported a rate of approximately 0.045%. 50 Gadolinium-based contrast agents do not cause as serious of an injury as iodinated-based agents, mainly due to the lower volume of material that is injected. 39…”
Section: Introductionmentioning
confidence: 99%